2020
DOI: 10.25177/jfst.5.6.ra.10684
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mycotoxins in botanicals: benefit and risk

Abstract: Background: Fusarium species are responsible for production of emerging mycotoxins with cyclic hexadepsispeptides structures, like enniatins and beauvericin. Although these mycotoxins have not been regulated yet, their high prevalence in food and feed, as well as their potential toxic effects in humans and animals have made of them a burning issue and a threat to food security. Besides its inophoric properties, these mycotoxins may induce cells damages such as oxidative stress, mitochondrial modifications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The cytotoxicity studies regarding their exposure to different cell lines revealed inhibitory concentration values (IC50) from 2.6 to 36 µM [ 11 ]. Despite their adverse effects on human and animal health, some beneficial properties have been attributed to ENNs, showing an interesting activity against various microorganisms and insects in several studies, leading to a potential use as biopesticides, as well as anticancer molecules combined with other drugs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity studies regarding their exposure to different cell lines revealed inhibitory concentration values (IC50) from 2.6 to 36 µM [ 11 ]. Despite their adverse effects on human and animal health, some beneficial properties have been attributed to ENNs, showing an interesting activity against various microorganisms and insects in several studies, leading to a potential use as biopesticides, as well as anticancer molecules combined with other drugs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%